Letter: opioid usage is associated with rectal hyposensitivity in patients with opioid‐induced constipation. Issue 4 (29th January 2023) - Vollebregt, Paul F.; Knowles, Charles H.; Scott, S. Mark
LINKED CONTENT: This article is linked to Cash et al paper. To view this article, visit https://doi.org/10.1111/apt.16702